Tissue adhesive material as well as preparation method and application thereof

By using the cross-linking reaction of acrylic and acrylamide monomers with modified chitosan compounds to form an interpenetrating network structure, the problems of slow adhesion speed and decreased mechanical properties of hydrogel adhesives are solved, achieving rapid adhesion and long-lasting adhesion on moist tissue surfaces, suitable for the closure and repair of tissue wounds.

CN121154894APending Publication Date: 2025-12-19MEDPRIN REGENERATIVE MEDICAL TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410796366.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2025-12-19

AI Technical Summary

Technical Problem

Existing hydrogel adhesives have slow adhesion speeds and are prone to water absorption, which leads to a decline in mechanical properties and adhesion. They cannot meet the requirements for good and durable adhesive strength in practical applications. Furthermore, the cytotoxicity of acrylic acid and its derivatives limits their application in tissue adhesive materials.

Method used

The polymer monomers used include acrylic and acrylamide monomers. The modified chitosan compounds are modified with polyphenolic compounds, and a photoinitiator and a free radical initiator are used to carry out two cross-linking reactions to form an interpenetrating network structure, which reduces monomer residue and improves biocompatibility and mechanical properties.

Benefits of technology

It achieves rapid adhesion on moist tissue surfaces, forming strong adhesion over a long period of time, and has good biocompatibility and mechanical properties, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121154894A_ABST
    Figure CN121154894A_ABST
Patent Text Reader

Abstract

The invention provides a tissue adhesive material as well as a preparation method and application thereof. The tissue bonding material is prepared from the following raw materials: a polymer monomer, wherein the polymer monomer comprises an acrylic monomer and an acrylamide monomer; the modified chitosan compound is obtained by modifying a chitosan compound through a polyphenol compound, and the polyphenol compound has two or more phenolic hydroxyl groups; and an initiator, wherein the initiator comprises a photoinitiator and a radical initiator. When the tissue bonding material is in contact with a wet or wet tissue surface, interface liquid existing between the bonding material and the wet tissue surface can be quickly absorbed and removed, and carboxyl, amido and catechol groups of the tissue bonding material can form a large number of molecular bonds with molecules on the wet tissue surface, so that instant bonding on the wet tissue surface is formed; and high adhesiveness can be maintained for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a kind of tissue adhesive material and its preparation method and use, belong to medical implant material field. BACKGROUND

[0002] At present, the closure of human tissue wound is handled by using suture or suture nail and other physical closure technology, but this closure technology can cause secondary trauma and postoperative inflammation, and can also cause infection due to poor wound sealing. In contrast, the tissue adhesive material has the characteristics of simple operation, short operation time, rapid wound healing, etc., and shows broad application prospects. The ideal tissue adhesive material should meet the following requirements: good biocompatibility and mechanical properties, good and durable adhesion strength in wet environment.

[0003] Hydrogel becomes a suitable material for wound treatment and repair due to its three-dimensional network structure, adjustable physicochemical properties and similar network structure to biological tissue. They can adhere to tissue, provide complete wound closure and become a barrier to bacterial infection. In addition, these materials absorb wound exudate and keep the wound moist to speed up the healing rate. At present, a variety of hydrogels have been developed for wound closure and repair, but long-term practice shows that the hydrogel adhesive still has the problems of slow adhesion speed, easy water absorption leading to the decline of mechanical properties and adhesion, and cannot meet the requirements of good and durable adhesion strength in actual use.

[0004] Polymers of acrylic acid and its derivatives have been widely studied in recent years due to their ideal wet-state tissue adhesion. However, due to the cytotoxicity of acrylic acid and its derivative monomers and the difficulty in removing them during preparation, their application in tissue adhesive materials is greatly limited. SUMMARY

[0005] Problems to be solved by the application

[0006] In view of the technical problems existing in the prior art, the present application first provides a tissue adhesive material.

[0007] The tissue adhesive material of the present application has good and durable tissue adhesion, biocompatibility, and excellent mechanical properties.

[0008] The present application also provides a preparation method of the tissue adhesive material, which is simple and easy to operate, and the raw materials are easy to obtain, suitable for mass production.

[0009] Solution for solving the problem

[0010] The present application provides a tissue adhesive material, and the preparation raw materials of the tissue adhesive material include:

[0011] a polymer monomer, the polymer monomer comprising an acrylic monomer and an acrylamide monomer;

[0012] a modified chitosan compound, the modified chitosan compound being obtained by modifying a chitosan compound with a polyphenol compound, wherein the polyphenol compound has two or more phenolic hydroxyl groups; and

[0013] an initiator, the initiator comprising a photoinitiator and a free radical initiator.

[0014] Further, the mass ratio of the acrylic monomer and the acrylamide monomer is (0.1-5):1, preferably (0.5-2):1.

[0015] Further, the polyphenol compound comprises one or a combination of two or more of 3-(3,4-dihydroxyphenyl)propionic acid, 2,3,4-trihydroxybenzaldehyde, dopamine, polydopamine, catechin, gallic acid, tannic acid, epicatechin, catechol, pyrogallol, and resveratrol.

[0016] Further, the mass ratio of the polymer monomer and the modified chitosan compound is (2-5):(0.5-2).

[0017] Further, the preparation raw materials further comprise an unmodified chitosan compound and / or a glycyrrhizic acid compound;

[0018] Preferably, the unmodified chitosan compound accounts for 2-15% of the total mass of the polymer monomer and the modified chitosan compound, and the glycyrrhizic acid compound accounts for 2-15% of the total mass of the polymer monomer and the modified chitosan compound.

[0019] Further, the tissue adhesive material is obtained by cross-linking reaction of the preparation raw materials;

[0020] Preferably, the tissue adhesive material is a sheet material.

[0021] Preferably, the tissue adhesive material has a breaking strength of 40 kPa or more; and / or

[0022] The tissue adhesive material has a swelling degree of 700% or less.

[0023] The present application also provides a preparation method of the tissue adhesive material according to the present application, comprising the following steps:

[0024] dissolving the polymer monomer, the modified chitosan compound, the optional unmodified chitosan compound, the optional glycyrrhizic acid compound, and the photoinitiator in a first solvent to obtain a precursor solution;

[0025] The precursor solution was subjected to a cross-linking reaction to obtain a hydrogel precursor.

[0026] The hydrogel precursor is immersed in a free radical initiator solution to carry out a secondary cross-linking reaction, thereby obtaining the hydrogel primary product.

[0027] The hydrogel sample is post-processed to obtain a tissue bonding material;

[0028] Preferably, the primary crosslinking reaction is carried out under ultraviolet or blue light irradiation, and the primary crosslinking reaction takes 20 to 120 minutes.

[0029] Preferably, the reaction temperature of the secondary crosslinking reaction is 40–80°C, and the reaction time is 10–60 min.

[0030] Furthermore, the method for preparing the modified chitosan compound includes modifying the chitosan compound with a polyphenol compound in the presence of a condensing agent.

[0031] Preferably, the method for preparing the modified chitosan compound includes the following steps:

[0032] Chitosan compounds are dissolved in a second solvent to obtain a chitosan compound solution;

[0033] A polyphenolic compound is added to the chitosan compound solution to obtain the reaction solution;

[0034] A condensing agent is added to the reaction solution for modification to obtain a modified chitosan compound.

[0035] Further, the post-processing includes:

[0036] The hydrogel sample was impregnated with an inorganic salt solution to obtain the impregnated product.

[0037] After removing unreacted acrylic monomers and / or acrylamide monomers from the impregnation product, the tissue adhesive material is obtained by drying and sterilization.

[0038] Preferably, the inorganic salt solution includes a saturated inorganic salt solution, more preferably a saturated sodium chloride solution;

[0039] Preferably, a buffer solution with a pH of 7 to 8 is used to remove unreacted acrylic monomers and / or acrylamide monomers from the impregnation product.

[0040] The present invention also provides the use of the tissue adhesive material according to the present invention in the preparation of hemostatic products, wound closure products, dura mater sealing products, vascular sealing products, lung sealing products, kidney sealing products, gastrointestinal anastomosis products, and cerebrospinal fluid leakage products.

[0041] The effects of the invention

[0042] When the tissue adhesive material of the present invention comes into contact with a moist or wet tissue surface, it can quickly absorb and remove the interfacial liquid between the adhesive material and the wet tissue surface. Furthermore, the carboxylic acid groups, amino groups, and catechol groups in the tissue adhesive material can form a large number of molecular bonds (such as hydrogen bonds, electrostatic interactions, and π bonds) with the molecules of the wet tissue surface, forming an instant adhesion to the wet tissue surface and maintaining strong adhesion for a long time.

[0043] In the tissue adhesive material of the present invention, the polymer monomers are polymerized under the action of a photoinitiator to form a first network. Then, by using a free radical initiator, the amino groups of the modified chitosan compound are covalently cross-linked with the carboxyl groups in the first network structure to form an interpenetrating network structure. Through two cross-linkings, the monomer residue in the tissue adhesive material is reduced, making the network structure of the tissue adhesive material more dense. The resulting tissue adhesive material has good and durable tissue adhesion, biocompatibility and mechanical properties, and low swelling degree.

[0044] The preparation method of the tissue adhesive material of the present invention is simple, easy to mold, and suitable for large-scale industrial production. Attached Figure Description

[0045] Figure 1 A product photograph of a tissue adhesive patch according to one embodiment of the present invention is shown. Detailed Implementation

[0046] Various exemplary embodiments, features, and aspects of the present invention will be described in detail below. The term "exemplary" as used herein means "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as superior to or better than other embodiments.

[0047] Furthermore, to better illustrate the present invention, numerous specific details are set forth in the following detailed embodiments. Those skilled in the art should understand that the present invention can be practiced without certain specific details. In other instances, methods, means, apparatus, and steps well known to those skilled in the art have not been described in detail in order to highlight the spirit of the present invention.

[0048] Unless otherwise stated, all units used in this specification are international standard units, and all numerical values ​​and ranges appearing in this invention should be understood to include systematic errors that are unavoidable in industrial production.

[0049] In this specification, the word "may" has two meanings: to perform a certain process and not to perform a certain process.

[0050] In this specification, references to "some specific / preferred embodiments," "other specific / preferred embodiments," "implementation," etc., refer to specific elements (e.g., features, structures, properties, and / or characteristics) related to that embodiment, which are included in at least one of the embodiments described herein and may or may not be present in other embodiments. Furthermore, it should be understood that these elements may be combined in any suitable manner in various embodiments.

[0051] In this specification, the range of values ​​referred to as "value A to value B" refers to the range including the endpoint values ​​A and B.

[0052] <First Aspect>

[0053] A first aspect of the present invention provides a tissue adhesive material, the raw materials for which are prepared include:

[0054] Polymer monomers, wherein the polymer monomers include acrylic monomers and acrylamide monomers;

[0055] A modified chitosan compound, wherein the modified chitosan compound is obtained by modifying the chitosan compound with a polyphenolic compound, wherein...

[0056] The polyphenolic compound has two or more phenolic hydroxyl groups; and

[0057] Initiators, including photoinitiators and free radical initiators.

[0058] The tissue adhesive material of the present invention has good adhesion and mechanical properties.

[0059] Polymer monomer

[0060] The polymer monomers of this invention include acrylic monomers and acrylamide monomers. In this invention, the acrylic monomers may be acrylic acid, and the acrylamide monomers may be acrylamide.

[0061] Furthermore, the polymer monomers of the present invention are not limited to acrylic monomers and acrylamide monomers, but preferably may also include methacrylic monomers and / or methacrylamide monomers. For example, exemplary methacrylic monomers may be methacrylic acid, carboxyethyl methacrylate, carboxypentyl methacrylate, and crotonic acid, etc.; exemplary methacrylamide monomers may be one or a combination of two or more of N-methacrylamide, N,N-dimethylacrylamide, N-hydroxyethylacrylamide, N-hydroxymethylacrylamide, etc.

[0062] In some specific embodiments, the mass ratio of the acrylic monomer to the acrylamide monomer is (0.1–5):1, preferably (0.5–2):1, for example: 0.2:1, 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, 3.2:1, 3.5:1, 3.8:1, 4:1, 4.2:1, 4.5:1, 4.8:1, etc. When the mass ratio of the acrylic monomer to the acrylamide monomer is (0.1–5):1, the electrostatic attraction between the acrylic monomer and the acrylamide monomer can form longer polymer molecular chains in the presence of a photoinitiator, resulting in a more stable molecular network and lower swelling degree.

[0063] Modified chitosan-based compound

[0064] The modified chitosan compound is obtained by modifying the chitosan compound with a polyphenolic compound. The inventors of this invention discovered that when the modified chitosan compound is placed in a buffer solution or solvent, the polyphenolic compound does not gradually dissolve, and the wet adhesiveness of the tissue bonding material can be effectively maintained. Therefore, this invention uses a modified chitosan compound.

[0065] To achieve good wet adhesion of tissue adhesive materials, this invention modifies chitosan compounds with polyphenolic compounds, resulting in modified chitosan compounds. By modifying chitosan compounds with polyphenolic compounds, phenolic hydroxyl groups can be introduced into the tissue adhesive material, which can react with amino groups and other groups on body tissues, thereby improving the wet adhesion of the tissue adhesive material.

[0066] In this invention, the polyphenolic compound has two or more phenolic hydroxyl groups. In some specific embodiments, the polyphenolic compound includes one or more combinations of 3-(3,4-dihydroxyphenyl)propionic acid, 2,3,4-trihydroxybenzaldehyde, dopamine, polydopamine, catechin, gallic acid, tannic acid, epicatechin, catechol, pyrogallol, and resveratrol.

[0067] Furthermore, the present invention does not specifically limit the chitosan compounds, and they can be chitosan compounds commonly used in the art, specifically including chitosan and / or chitosan derivatives; preferably, the chitosan derivatives include carboxymethyl chitosan and / or carboxyethyl chitosan.

[0068] In some specific embodiments, the mass ratio of the polymer monomer to the modified chitosan compound is (2-5):(0.5-2), for example: 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, etc. When the mass ratio of the polymer monomer to the modified chitosan compound is (2-5):(0.5-2), the tissue adhesive material exhibits good wet adhesion and excellent mechanical properties.

[0069] Initiator

[0070] The initiators of this invention include photoinitiators and free radical initiators. This invention uses a photoinitiator to copolymerize and crosslink acrylic and acrylamide monomers to form a first network structure. Then, using a free radical initiator, the amino groups of the modified chitosan compound are covalently crosslinked with the carboxyl groups in the first network structure, thereby forming an interpenetrating network structure. Through two copolymerization and crosslinking processes, the crosslinking density can be increased. The swelling degree of the tissue adhesive material obtained by two copolymerization and crosslinking processes is significantly lower than that of the tissue adhesive material prepared by a single polymerization process, and monomer residue is reduced, thus improving biocompatibility.

[0071] Furthermore, this invention can achieve a first crosslinking under ultraviolet light using a photoinitiator, followed by a second crosslinking via a free radical reaction. Using two initiators allows for the polymerization of polymer monomers as efficiently as possible to reduce toxicity. Simultaneously, the free radical reaction enables covalent crosslinking of amino and carboxyl groups, resulting in a more complex polymer network structure to counteract swelling and reduce the swelling degree of the tissue adhesive material.

[0072] In some specific embodiments, the photoinitiator of the present invention includes one or more combinations selected from α-ketoglutaric acid, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone (Irgacure 2959), bis(pentafluorophenyl)titanium, diphenyltitanium fluoride (Irgacure 784), and lithium phenyl-2,4,6-trimethylbenzoylphosphine (LAP).

[0073] In some specific embodiments, the free radical initiator of the present invention comprises a selection of inorganic persulfate compounds and / or azo compounds, wherein the inorganic persulfate preferably comprises persulfates, such as ammonium persulfate, potassium persulfate, sodium persulfate, etc.; and the azo compound is preferably azobisisobutyronitrile, azobisisobutylamidine, azobisisoheptanenitrile, azobisisovalerate, azobiscyclohexylformitrile, dimethyl azobisisobutyrate, etc.

[0074] Other substances

[0075] The tissue adhesive material of the present invention may further include unmodified chitosan compounds and / or glycyrrhizic acid compounds.

[0076] The present invention does not specifically limit the unmodified chitosan compounds, which can be chitosan compounds commonly used in the art, specifically including chitosan and / or chitosan derivatives; preferably, the chitosan derivatives include carboxymethyl chitosan and / or carboxyethyl chitosan.

[0077] By adding unmodified chitosan compounds, the amine groups on the chitosan compounds can be further covalently crosslinked with the carboxyl groups on the first network structure, thereby increasing the crosslinking density and further reducing the swelling degree.

[0078] Preferably, the unmodified chitosan compound accounts for 2-15% of the total mass of the polymer monomer and the modified chitosan compound, for example: 3%, 5%, 7%, 9%, 11%, 13%, etc. When the unmodified chitosan compound accounts for 2-15% of the total mass of the polymer monomer and the modified chitosan compound, the swelling degree of the tissue adhesive material can be further reduced.

[0079] For glycyrrhizic acid compounds, specifically glycyrrhizic acid and / or glycyrrhizic acid derivatives, preferably, the glycyrrhizic acid derivatives may include glycyrrhizic acid monoammonium salt and / or glycyrrhizic acid dipotassium salt.

[0080] This invention further reduces the swelling degree of tissue adhesive materials by adding glycyrrhizic acid compounds. Glycyrrhizic acid compounds are amphiphilic molecules rich in carboxyl groups, composed of hydrophilic glucuronic acid and hydrophobic glycyrrhetinic acid. This amphiphilic structure allows them to self-assemble, producing hydrogels with a nanofiber network structure in water. This enables the hydrogels to form more interpenetrating network structures, resulting in smaller porosity and reduced swelling degree.

[0081] Preferably, the glycyrrhizic acid compound accounts for 2-15% of the total mass of the polymer monomer and the modified chitosan compound, for example: 3%, 5%, 7%, 9%, 11%, 13%, etc. When the glycyrrhizic acid compound accounts for 2-15% of the total mass of the polymer monomer and the modified chitosan compound, the glycyrrhizic acid compound can effectively exert its function.

[0082] Tissue adhesive material

[0083] The tissue adhesive material of the present invention is obtained by cross-linking reaction of raw materials; preferably, the tissue adhesive material is a sheet material.

[0084] The tissue adhesive material of the present invention has a breaking strength of 40 kPa or more, preferably 40 kPa to 100 kPa. The swelling degree of the tissue adhesive material is 700% or less, more preferably 500% or less.

[0085] In addition, the residual rate of acrylic acid and the residual rate of acrylamide in the tissue adhesive material of the present invention are both less than 0.03%.

[0086] The tissue adhesive material of this invention is obtained by two crosslinking reactions of raw materials. The polymer monomers polymerize under the action of a photoinitiator to form a first network. Then, a free radical initiator is used to covalently crosslink the amino groups of the modified chitosan compound with the carboxyl groups in the first network structure, thereby forming an interpenetrating network structure. Through these two crosslinking processes, the monomer residue in the tissue adhesive material is reduced, resulting in a denser network structure. The resulting tissue adhesive material exhibits good and durable tissue adhesion, biocompatibility, and mechanical properties, and also has low swelling.

[0087] <Second aspect>

[0088] A second aspect of the present invention provides a method for preparing a tissue adhesive material according to the first aspect of the present invention, comprising the following steps:

[0089] The polymer monomer, modified chitosan compound, optional unmodified chitosan compound, optional glycyrrhizic acid compound and photoinitiator are dissolved in a first solvent to obtain a precursor solution;

[0090] The precursor solution was subjected to a cross-linking reaction to obtain a hydrogel precursor.

[0091] The hydrogel precursor was immersed in a free radical initiator solution to carry out a secondary cross-linking reaction, thereby obtaining the hydrogel primary product.

[0092] The hydrogel sample was post-processed to obtain a tissue bonding material.

[0093] The preparation method of the tissue adhesive material of the present invention is simple, easy to mold, and suitable for large-scale industrial production.

[0094] Preparation of modified chitosan-based compound

[0095] In this invention, the method for preparing the modified chitosan compound includes modifying the chitosan compound with a polyphenol compound in the presence of a condensing agent.

[0096] In some specific embodiments, the preparation method of the modified chitosan compound includes the following steps:

[0097] Chitosan compounds are dissolved in a second solvent to obtain a chitosan compound solution;

[0098] A polyphenolic compound is added to the chitosan compound solution to obtain the reaction solution;

[0099] A condensing agent is added to the reaction solution for modification to obtain a modified chitosan compound.

[0100] The present invention does not particularly limit the second solvent, which can be water or an acidic solvent. The acidic solvent is generally obtained by dissolving an acidic substance in water or other polar solvents. Specifically, the acidic substance can be one or a combination of two or more of hydrochloric acid, sulfuric acid, acetic acid, etc. The molar concentration of the acidic substance in the acidic solvent can be 0.1–1 mol / L, for example: 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, etc.

[0101] The chitosan compound solution contains chitosan compounds at a mass concentration of 0.5% to 2%, for example, 0.8%, 1%, 1.2%, 1.5%, 1.8%, etc. Further, polyphenolic compounds are added to the chitosan compound solution to obtain a reaction solution. At this point, only the chitosan compound and polyphenolic compound are brought into contact. Next, a condensing agent is added to the reaction solution for modification treatment to obtain a modified chitosan compound. The addition of the condensing agent ensures that the modification treatment can proceed effectively.

[0102] The present invention does not impose any particular limitation on the amount of polyphenolic compounds used, and the amount can be set as needed. Generally speaking, the mass ratio of chitosan compounds to polyphenolic compounds can be 1:(1 to 8), for example, 1:2, 1:4, 1:6, etc.

[0103] In some specific implementation schemes, in order to obtain a reaction solution that is more conducive to subsequent reactions, the pH value of the reaction solution can be adjusted to 4.5-5.

[0104] Specifically, the condensing agent may include carbodiimide compounds, preferably one or a combination of two or more of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N,N'-dicyclohexylcarbodiimide and N,N'-diisopropylcarbodiimide.

[0105] The present invention does not specify the amount of condensing agent to be added, but it can be set as needed. Generally speaking, the mass ratio of chitosan compound to condensing agent can be 1:(3 to 10), such as 1:5, 1:7, 1:9, etc.

[0106] In some specific embodiments, to better integrate the condensing agent with the reaction solution, the condensing agent can be dissolved in an alcohol solvent to obtain a condensing agent solution. The alcohol solvent can be a commonly used alcohol solvent in the art, such as ethanol, propanol, ethylene glycol, propylene glycol, triglycerides, etc. To further improve the dissolution of the condensing agent, an aqueous solution of the alcohol solvent can be used. The mass concentration of the alcohol solvent in the aqueous solution can be 30-80%, for example: 40%, 50%, 60%, 70%, etc.

[0107] Furthermore, a condensing agent solution buffer is added dropwise to the reaction mixture to allow the modification process to proceed effectively, resulting in a modified chitosan compound.

[0108] Precursor solution

[0109] This invention involves dissolving a polymer monomer, a modified chitosan compound, an optional unmodified chitosan compound, an optional glycyrrhizic acid compound, and a photoinitiator in a first solvent to obtain a precursor solution. The concentrations of the polymer monomer, modified chitosan compound, unmodified chitosan compound, glycyrrhizic acid compound, and photoinitiator are not particularly limited and can be set as needed, as long as the chemical reaction can proceed effectively.

[0110] The present invention does not particularly limit the first solvent, which is generally a polar solvent commonly used in the art, such as water.

[0111] In this invention, based on the total mass of the precursor solution as 100%, the content of the polymer monomer is 20-50%, the content of the modified chitosan compound is 5-20%, the content of the photoinitiator is 0.2-1.5%, the content of the unmodified chitosan compound is 0-5%, and the content of the glycyrrhizic acid compound is 0-5%. When the content of each component in the precursor solution of this invention is within the above ranges, it is beneficial to the subsequent crosslinking polymerization.

[0112] Cross-linking polymerization

[0113] The tissue bonding material can be prepared using a substrate. The material of the substrate is not particularly limited in this invention; it can generally be glass, such as a glass plate. Specifically, the precursor solution can be placed on the surface of the substrate, forming a layer of the precursor solution to be reacted on the substrate surface. The method of placing the precursor solution on the surface of the substrate is not particularly limited in this invention; it can be done by casting, spraying, coating, etc., as long as the precursor solution can be continuously present on the surface of the substrate.

[0114] Furthermore, the precursor solution on the surface of the substrate undergoes a primary crosslinking reaction to obtain a hydrogel material precursor. Specifically, the primary crosslinking reaction is carried out under ultraviolet or blue light irradiation; preferably, the time for the primary crosslinking reaction can be 20–120 min, for example: 40 min, 60 min, 80 min, 100 min, etc. Specifically, the wavelength of ultraviolet light can be 350–380 nm, and the wavelength of blue light can be 400 nm–480 nm.

[0115] In some specific implementations, after the first crosslinking reaction, the precursor can be dried to obtain a hydrogel precursor, which is more effectively capable of secondary crosslinking. The hydrogel precursor is then immersed in a free radical initiator solution to undergo a secondary crosslinking reaction, yielding a preliminary hydrogel product.

[0116] The present invention does not impose a particular limitation on the amount of the free radical initiator solution used, as long as it is sufficient to completely immerse the hydrogel precursor. Specifically, the concentration of the free radical initiator in the free radical initiator solution can be 5-20% by mass, for example: 8% by mass, 10% by mass, 12% by mass, 15% by mass, 18% by mass, etc.

[0117] In some specific implementations, the reaction temperature of the secondary crosslinking reaction is 40-80°C, for example: 40°C, 50°C, 60°C, 70°C, etc.; the reaction time is 10-60 min, for example: 20 min, 30 min, 40 min, 50 min, etc.

[0118] Post-treatment

[0119] This invention further promotes the entanglement of modified chitosan compounds and / or chitosan chain molecules by post-processing the initial hydrogel material, thereby increasing mechanical properties and resisting swelling, resulting in a tissue bonding material with superior performance.

[0120] In some specific embodiments, the post-processing includes impregnating the hydrogel sample with an inorganic salt solution to obtain an impregnated product. Specifically, the hydrogel sample is immersed in an inorganic salt solution to obtain the impregnated product.

[0121] The inventors of this invention have discovered that by using an inorganic salt solution, the entanglement of modified chitosan compounds and / or the chain molecules of chitosan compounds can be further promoted, thereby increasing mechanical properties while reducing swelling.

[0122] The present invention does not impose any particular limitation on the concentration of inorganic salts in the inorganic salt solution, and it can be set as needed. In order to enable the post-processing function to function effectively, the inorganic salt solution used in the present invention is preferably a saturated inorganic salt solution, such as a saturated sodium chloride solution and / or a saturated potassium chloride solution.

[0123] The present invention does not impose a particular limitation on the soaking time, but generally it is at a temperature below 10°C, for example 0 to 10°C, for soaking for more than 12 hours, for example 12 to 36 hours.

[0124] Further, unreacted acrylic monomers and / or acrylamide monomers are removed from the impregnation product to obtain a tissue adhesive material.

[0125] In some specific implementations, a buffer solution with a pH of 7-8 can be used to remove unreacted acrylic monomers and / or acrylamide monomers from the impregnation product. The buffer solution is typically a PBS buffer solution.

[0126] Specifically, the impregnation product is placed in a buffer solution to remove unreacted acrylic monomers and / or acrylamide monomers.

[0127] Generally speaking, the temperature of the buffer solution can be 35-40°C, and the time for the immersion product to be placed in the buffer solution can be more than 12 hours, for example, 12-36 hours.

[0128] Finally, the tissue adhesive material is dried, sealed and packaged, and then sterilized by Co-60 gamma irradiation to obtain the tissue adhesive material.

[0129] <Third aspect>

[0130] A third aspect of the present invention provides the use of the tissue adhesive material according to the first aspect of the present invention in the preparation of hemostatic products, wound closure products, dura mater sealing products, vascular sealing products, lung sealing products, kidney sealing products, gastrointestinal anastomosis products, and cerebrospinal fluid leakage products.

[0131] Example

[0132] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0133] Example 1

[0134] (1) Synthesis of modified chitosan:

[0135] Dissolve 2g of chitosan in 120mL of 0.5mol / L hydrochloric acid solution and stir until completely dissolved. Then add 6g of 3-(3,4-dihydroxyphenyl)propionic acid and adjust the pH to 4.5-5 to obtain solution I.

[0136] Dissolve 10g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide in 20mL of 50% ethanol aqueous solution to obtain solution II;

[0137] Solution II was slowly added dropwise to solution I, and after thorough stirring, the mixture was reacted overnight at room temperature. After dialyzing, the mixture was lyophilized to obtain modified chitosan powder for later use.

[0138] (2) Preparation of tissue adhesive patches:

[0139] Dissolve 3g of acrylic acid, 3g of acrylamide, and 1g of modified chitosan in 5mL of purified water and stir at 60℃ until dissolved; add 0.05g of α-ketoglutarate and stir to dissolve to obtain the precursor solution;

[0140] The above precursor solution was cast onto a 12×12cm glass plate, irradiated with 365nm ultraviolet light for 30min, dried, and then immersed in 50mL of 20% by mass ammonium persulfate solution. The reaction was carried out at 60℃ for 30min to obtain the initial hydrogel product.

[0141] The initial hydrogel sample was immersed in a saturated sodium chloride solution and stored at 4°C for 24 hours, followed by immersion in PBS solution at 37°C for 24 hours to remove unreacted acrylic monomers. After drying, it was sealed and packaged, and then sterilized by Co-60 gamma irradiation to obtain tissue adhesion patches, the morphology of which is as follows. Figure 1 As shown.

[0142] Example 2

[0143] Synthetic modified chitosan:

[0144] Dissolve 2g of chitosan in 120mL of 0.5mol / L hydrochloric acid solution and stir until completely dissolved. Then add 6g of 3-(3,4-dihydroxyphenyl)propionic acid and adjust the pH to 4.5-5 to obtain solution I.

[0145] Dissolve 10g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide in 20mL of 50% ethanol aqueous solution to obtain solution II;

[0146] Solution II was slowly added dropwise to solution I, and after thorough stirring, the mixture was reacted overnight at room temperature. After dialyzing, the mixture was lyophilized to obtain modified chitosan powder for later use.

[0147] (2) Preparation of tissue adhesive patches:

[0148] Dissolve 3g of acrylic acid, 3g of acrylamide, 0.2g of chitosan, and 1g of modified chitosan in 5mL of purified water and stir at 60℃ until dissolved; add 0.05g of α-ketoglutaric acid and stir to dissolve to obtain the precursor solution;

[0149] The above precursor solution was cast onto a 12×12cm glass plate, irradiated with 365nm ultraviolet light for 30min, dried, and then immersed in 50mL of 20% by mass ammonium persulfate solution. The reaction was carried out at 60℃ for 30min to obtain the initial hydrogel product.

[0150] The initial hydrogel sample was immersed in a saturated sodium chloride solution and stored at 4°C for 24 hours. Then it was immersed in PBS solution at 37°C for 24 hours to remove unreacted acrylic monomers. After drying, it was sealed and packaged, and then sterilized by Co-60 γ-ray irradiation to obtain tissue adhesion patches.

[0151] Example 3

[0152] (1) Synthesis of modified chitosan

[0153] Dissolve 2g of chitosan in 120mL of 0.5mol / L hydrochloric acid solution, stir until completely dissolved, add 6g of 3-(3,4-dihydroxyphenyl)propionic acid, and adjust the pH to 4.5-5 to obtain solution I;

[0154] Dissolve 10g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide in 20mL of 50% ethanol aqueous solution to obtain solution II;

[0155] Solution II was slowly added dropwise to solution I, and after thorough stirring, the mixture was reacted overnight at room temperature. After dialyzing, the mixture was lyophilized to obtain modified chitosan powder for later use.

[0156] (2) Preparation of tissue adhesive patches:

[0157] Dissolve 3g of acrylic acid, 3g of acrylamide, 1g of modified chitosan, and 0.2g of glycyrrhizic acid in 5mL of purified water and stir at 60℃ until dissolved; then add 0.05g of α-ketoglutaric acid and stir to dissolve to obtain the precursor solution;

[0158] The above precursor solution was cast onto a 12×12cm glass plate, irradiated with 365nm ultraviolet light for 30min, dried, and then immersed in 50mL of 20% by mass ammonium persulfate solution. The reaction was carried out at 60℃ for 30min to obtain the initial hydrogel product.

[0159] The initial hydrogel sample was immersed in a saturated sodium chloride solution and stored at 4°C for 24 hours; then it was immersed in a PBS solution at 37°C for 24 hours to remove unreacted acrylic monomers, then dried, sealed and packaged, and sterilized by Co-60 γ-ray irradiation to obtain tissue adhesion patches.

[0160] Example 4

[0161] Synthetic modified chitosan

[0162] Dissolve 2g of chitosan in 120mL of 0.5mol / L hydrochloric acid solution and stir until completely dissolved. Then add 6g of 3-(3,4-dihydroxyphenyl)propionic acid and adjust the pH to 4.5-5 to obtain solution I.

[0163] Dissolve 10g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide in 20mL of 50% ethanol aqueous solution to obtain solution II;

[0164] Solution II was slowly added dropwise to solution I, and after thorough stirring, the mixture was reacted overnight at room temperature. After dialyzing, the mixture was lyophilized to obtain modified chitosan powder for later use.

[0165] (2) Preparation of tissue adhesive patches:

[0166] Dissolve 3g acrylic acid, 3g acrylamide, 0.2g chitosan, 1g modified chitosan, and 0.2g glycyrrhizic acid in 5mL of purified water and stir at 60℃ until dissolved; then add 0.05g of α-ketoglutaric acid and stir to dissolve to obtain the precursor solution;

[0167] The above precursor solution was cast onto a 12×12cm glass plate, irradiated with 365nm ultraviolet light for 30min, dried, and then immersed in 50mL of 20% by mass ammonium persulfate solution. The reaction was carried out at 60℃ for 30min to obtain the initial hydrogel product.

[0168] The initial hydrogel sample was immersed in a saturated sodium chloride solution and stored at 4°C for 24 hours; then it was immersed in a PBS solution at 37°C for 24 hours to remove unreacted acrylic monomers, then dried, sealed and packaged, and sterilized by Co-60 γ-ray irradiation to obtain tissue adhesion patches.

[0169] Example 5

[0170] Synthetic modified chitosan

[0171] Dissolve 1g of carboxymethyl chitosan in 120mL of water and stir until completely dissolved. Then add 6g of 2,3,4-trihydroxybenzaldehyde and adjust the pH to 4.5-5 to obtain solution I.

[0172] Dissolve 10g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide in 20mL of 50% ethanol aqueous solution to obtain solution II;

[0173] Solution II was slowly added dropwise to solution I, and after thorough stirring, the mixture was reacted overnight at room temperature. After dialyzing, the mixture was lyophilized to obtain modified chitosan powder for later use.

[0174] (2) Preparation of tissue adhesive patches:

[0175] Dissolve 1.5g of acrylic acid, 3g of acrylamide, and 1.7g of modified chitosan in 6.5mL of purified water and stir at 60℃ until dissolved; then add 0.1g of bis(pentafluorophenyl)titanium oxide and stir to dissolve to obtain the precursor solution;

[0176] The above precursor solution was cast onto a 12×12cm glass plate, irradiated with 365nm ultraviolet light for 60min, dried, and then immersed in 50mL of 6% potassium persulfate solution. The reaction was carried out at 60℃ for 30min to obtain the initial hydrogel product.

[0177] The initial hydrogel sample was immersed in a saturated sodium chloride solution and stored at 4°C for 24 hours; then it was immersed in a PBS solution at 37°C for 24 hours to remove unreacted acrylic monomers, then dried, sealed and packaged, and sterilized by Co-60 γ-ray irradiation to obtain tissue adhesion patches.

[0178] Example 6

[0179] Synthetic modified chitosan

[0180] Dissolve 3g of carboxymethyl chitosan in 120mL of water and stir until completely dissolved. Then add 4g of dopamine and adjust the pH to 4.5-5 to obtain solution I.

[0181] Dissolve 10g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide in 20mL of 50% ethanol aqueous solution to obtain solution II;

[0182] Solution II was slowly added dropwise to solution I, and after thorough stirring, the mixture was reacted overnight at room temperature. After dialyzing, the mixture was lyophilized to obtain modified chitosan powder for later use.

[0183] (2) Preparation of tissue adhesive patches:

[0184] Take 2g of acrylic acid, 1g of acrylamide, 1.2g of modified chitosan, 0.6g of chitosan and 0.6g of glycyrrhizic acid and dissolve them in 7mL of purified water. Stir at 60℃ until dissolved. Then add 0.1g of phenyl-2,4,6-trimethylbenzoyl lithium phosphine and stir to dissolve to obtain the precursor solution.

[0185] The above precursor solution was cast onto a 12×12cm glass plate, irradiated with 365nm ultraviolet light for 80min, dried, and then immersed in 50mL of 16% sodium persulfate solution. The reaction was carried out at 60℃ for 20min to obtain the initial hydrogel product.

[0186] The initial hydrogel sample was immersed in a saturated sodium chloride solution and stored at 4°C for 24 hours; then it was immersed in a PBS solution at 37°C for 24 hours to remove unreacted acrylic monomers, then dried, sealed and packaged, and sterilized by Co-60 γ-ray irradiation to obtain tissue adhesion patches.

[0187] Comparative Example 1

[0188] Take 3g of acrylic acid, 3g of acrylamide, 0.2g of chitosan, and 200μL of hydrochloric acid, dissolve them in 6mL of purified water, and stir at 60℃ until dissolved; then add 0.05g of α-ketoglutaric acid, stir to dissolve, and obtain the precursor solution;

[0189] The above precursor solution was cast onto a 12×12cm glass plate, irradiated with 365nm ultraviolet light for 30min, dried, and then immersed in 50mL of 20% by mass ammonium persulfate solution. The reaction was carried out at 60℃ for 30min to obtain the initial hydrogel product.

[0190] The initial hydrogel sample was immersed in a saturated sodium chloride solution and stored at 4°C for 24 hours; then it was immersed in a PBS solution at 37°C for 24 hours to remove unreacted acrylic monomers, then dried, sealed and packaged, and sterilized by Co-60 γ-ray irradiation to obtain tissue adhesion patches.

[0191] Comparative Example 2

[0192] Take 3g of acrylic acid, 3g of acrylamide, 0.2g of chitosan, 0.3g of 3-(3,4-dihydroxyphenyl)propionic acid, and 200μL of hydrochloric acid, dissolve them in 6mL of purified water, and stir at 60℃ until dissolved; then add 0.05g of α-ketoglutaric acid, stir to dissolve, and obtain the precursor solution;

[0193] The above precursor solution was cast onto a 12×12cm glass plate, irradiated with 365nm ultraviolet light for 30min, dried, and then immersed in 50mL of 20% by mass ammonium persulfate solution. The reaction was carried out at 60℃ for 30min to obtain the initial hydrogel product.

[0194] The initial hydrogel sample was immersed in a saturated sodium chloride solution and stored at 4°C for 24 hours; then it was immersed in a PBS solution at 37°C for 24 hours to remove unreacted acrylic monomers, then dried, sealed and packaged, and sterilized by Co-60 γ-ray irradiation to obtain tissue adhesion patches.

[0195] Comparative Example 3

[0196] Dissolve 3g of acrylic acid and 1g of modified chitosan in 5mL of purified water and stir until dissolved; then add 0.05g of α-ketoglutarate and stir until dissolved to obtain the precursor solution;

[0197] The above precursor solution was cast onto a 12×12cm glass plate, irradiated with 365nm ultraviolet light for 30min, dried, and then immersed in 50mL of 20% by mass ammonium persulfate solution. The reaction was carried out at 60℃ for 30min to obtain the initial hydrogel product.

[0198] The initial hydrogel sample was immersed in a saturated sodium chloride solution and stored at 4°C for 24 hours; then it was immersed in a PBS solution at 37°C for 24 hours to remove unreacted acrylic monomers, then dried, sealed and packaged, and sterilized by Co-60 γ-ray irradiation to obtain tissue adhesion patches.

[0199] Performance test

[0200] 1. Continuous adhesion test under wet conditions

[0201] The adhesive occlusion effect and duration of occlusion of tissue adhesive patches are important in vitro performance evaluations. These represent the minimum pressure required to cause rupture or bursting of the tissue sealed by the patch, and the duration of that pressure. This characteristic becomes particularly important when tissue adhesive patches are used to prevent leakage from wounds in tissues such as the heart, lungs, or gastrointestinal tract.

[0202] Test method: The test was conducted using a gel pressure resistance test recording fixture system. The specific method is as follows:

[0203] First, take a 4cm diameter sausage casing and prepare a 5mm diameter hole in the center. Adhere the tissue adhesive patch (15mm × 15mm) from the examples and comparative examples to the wound. During adhesion, ensure the midline of the tissue adhesive patch is directly above the incision. Maintain a pressure of 4 kPa and use a pump to drop PBS solution onto the tissue adhesive patch at a rate of 2 mL / min. The test period is 14 days, observing whether the sample can maintain pressure. The experimental results are shown in Table 1.

[0204] Table 1 Adhesion test results

[0205] Experimental sample 1 day 7 days 14 days Example 1 sample The pressure was maintained. The pressure was maintained. The pressure was maintained. Example 2 sample The pressure was maintained. The pressure was maintained. The pressure was maintained. Example 3 sample The pressure was maintained. The pressure was maintained. The pressure was maintained. Example 4 sample The pressure was maintained. The pressure was maintained. The pressure was maintained. Example 5 sample The pressure was maintained. The pressure was maintained. The pressure was maintained. Example 6 sample The pressure was maintained. The pressure was maintained. The pressure was maintained. Comparative example 1 sample The pressure was lost. / / Comparative example 2 sample The pressure was lost. / / Comparative example 3 sample The pressure was lost. / /

[0206] As can be seen from Table 1, the tissue adhesive patch of the present invention can still maintain pressure on the 7th day and even the 14th day, and its adhesion is far superior to that of comparative examples 1-3.

[0207] 2. Mechanical property testing

[0208] Burst pressure is an important mechanical property of tissue adhesive patches, representing the minimum pressure required to cause the tissue sealed by the patch to rupture or burst. This property becomes particularly important when tissue adhesive patches are used to prevent leakage from wounds in tissues such as the heart, lungs, or gastrointestinal tract. Generally, a burst strength of 6.7 kPa is required to prevent cerebrospinal fluid leakage, 4 kPa to prevent pulmonary leakage, and 18.8 kPa to prevent vascular bleeding.

[0209] The testing method is as follows:

[0210] (1) The testing equipment consists of a base (containing a water tank), a fixed hollow cover, a water delivery system, and a pressure testing system. Take a sausage casing with a diameter of not less than 4 cm and prepare a 5 mm diameter hole in the center of the casing. Draw a dot on the test table using an oil-based pen and place the hole at the center of the dot. Take the samples prepared in the examples and comparative examples, cut out a 1.5 cm diameter circular test specimen using a 1.5 cm diameter skin biopsy device, place the sample on the sausage casing with the small hole as the center, and ensure it adheres to the casing to form a seal. Then place it on the test base, fix it with the hollow cover, and apply external pressure to measure the bursting strength. Bursting strength is the combined effect of the elasticity, toughness, and adhesion of the tissue adhesive patch itself.

[0211] (2) Bursting strength test: Turn on the water delivery system and inject PBS solution at a rate of 2 mL / min to increase the pressure. Record the maximum pressure at which the sample ruptures and fails. The test results are shown in Table 2.

[0212] Table 2 Results of fracture strength test

[0213] Experimental sample Breaking strength (kPa) Example 1 sample 64.49 Example 2 sample 48.94 Example 3 sample 45.88 Example 4 sample 96.19 Example 5 sample 60.52 Example 6 sample 92.67 Comparative example 1 sample 37.71 Comparative example 2 sample 42.52 Comparative example 3 sample 37.79

[0214] The tissue adhesive patches of Examples 1-6 of the present invention have higher breaking strength than those of Comparative Examples 1-3, and their mechanical properties are superior.

[0215] 3. Swelling degree test

[0216] Approximately 1g of the tissue adhesive patch from the examples and comparative examples was accurately weighed, and its mass was denoted as W. i Add phosphate buffer solution at a ratio of 1g:30mL, soak for 24 hours, remove the gel, blot off excess water with filter paper, and weigh it, denoted as W. t The swelling degree was calculated according to formula (1), and the results are shown in Table 3.

[0217] SR = (W t -W i ) / W i ×100% (1)

[0218] In equation (1): SR represents the swelling degree of the gel; Wt Indicates the mass of the gel after swelling; W i This indicates the mass of the gel before swelling.

[0219] Table 3. Results of swelling degree test

[0220] Experimental sample Swelling degree (%) Example 1 sample 464% Example 2 sample 408% Example 3 sample 396% Example 4 sample 361% Example 5 sample 460% Example 6 sample 306% Comparative example 1 sample 3403% Comparative example 2 sample 2178% Comparative example 3 sample 4057%

[0221] The swelling degree of the tissue adhesive materials in Examples 1-6 of the present invention is less than 500%, that is, less than 5 times, which is much lower than that of Comparative Examples 1-3.

[0222] 4. Acrylic acid residue test

[0223] Acrylic acid was determined by gas chromatography.

[0224] Test solution: Cut the tissue adhesive patch into small pieces, accurately weigh 30 mg, add 2 ml of acetic acid PBS solution (4.5 μg acetic acid / mL PBS), soak for 3 days, then add 8 ml of acetic acid methanol solution (4.5 μg acetic acid / mL methanol), mix well, filter, and collect the filtrate.

[0225] Acrylic acid reference solution: Accurately transfer 0.5 ml of 450 ug / mL acrylic acid stock solution and 0.5 ml of 450 ug / mL acetic acid stock solution into a 50 ml volumetric flask, add 10 ml of PBS, dilute to the mark with methanol, and mix well. The concentrations of acrylic acid and acetic acid are 4.5 ug / ml.

[0226] The chromatographic column used was an EG-WAX column, 0.25mm*30m, 0.25um, with nitrogen as the carrier gas (1.5mL / min). The test sample and reference solution were manually injected at a split ratio of 2:1 and an injection volume of 5μL.

[0227] Table 4 Results of Acrylic Acid Residue Detection

[0228] Experimental sample Acrylic acid residue % Example 1 sample 0.025 Example 2 sample 0.027 Example 3 sample 0.028 Example 4 sample 0.010 Example 5 sample 0.025 Example 6 sample 0.013 Comparative example 1 sample 0.032 Comparative example 2 sample 0.033 Comparative example 3 sample 0.031

[0229] As can be seen from Table 4, the acrylic acid residue of the tissue adhesive patches of Examples 1-6 of the present invention is less than 0.03%, and is also lower than that of Comparative Examples 1-3.

[0230] 5. Acrylamide Residue Test

[0231] Acrylamide was determined by gas chromatography.

[0232] Test solution: Cut the tissue adhesive patch into small pieces, accurately weigh 30 mg, add 2 ml DMF PBS solution (4.5 ug DMF / mL PBS), soak for 3 days, then add 8 ml DMF methanol solution (4.5 ug DMF / mL methanol), mix well, filter, and collect the filtrate.

[0233] Acrylamide reference solution: Accurately transfer 0.5 ml of 450 ug / mL acrylamide stock solution and 0.5 ml of 450 ug / mL DMF stock solution into a 50 ml volumetric flask, add 10 ml of PBS, dilute to the mark with methanol, and mix well. The acrylamide concentration is 4.5 ug / ml and the DMF concentration is 4.5 ug / ml.

[0234] The chromatographic column used was an EG-WAX column, 0.25mm*30m, 0.25um, with nitrogen as the carrier gas (1.5mL / min). The test sample and reference solution were manually injected at a split ratio of 2:1 and an injection volume of 5μL.

[0235] Table 5 Acrylamide Residue Detection Results

[0236] Experimental sample Acrylamide residue % Example 1 sample 0.022 Example 2 sample 0.024 Example 3 sample 0.028 Example 4 sample 0.020 Example 5 sample 0.025 Example 6 sample 0.021 Comparative example 1 sample 0.035 Comparative example 2 sample 0.044 Comparative example 3 sample /

[0237] As can be seen from Table 5, the acrylamide residue of the tissue adhesive patches of Examples 1-6 of the present invention is less than 0.03%, and is also lower than that of Comparative Examples 1-2.

[0238] It should be noted that although the technical solution of the present invention has been described with specific examples, those skilled in the art will understand that the present invention should not be limited thereto.

[0239] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or technical improvements to the embodiments in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.

Claims

1. A tissue bonding material, characterized in that, The raw materials for preparing the tissue adhesive material include: Polymer monomers, wherein the polymer monomers include acrylic monomers and acrylamide monomers; A modified chitosan compound, wherein the modified chitosan compound is obtained by modifying the chitosan compound with a polyphenolic compound, wherein the polyphenolic compound has two or more phenolic hydroxyl groups; and Initiators, including photoinitiators and free radical initiators.

2. The tissue adhesive material according to claim 1, characterized in that, The mass ratio of the acrylic monomer to the acrylamide monomer is (0.1-5):1, preferably (0.5-2):

1.

3. The tissue adhesive material according to claim 1 or 2, characterized in that, The polyphenolic compounds include one or more of the following: 3-(3,4-dihydroxyphenyl)propionic acid, 2,3,4-trihydroxybenzaldehyde, dopamine, polydopamine, catechin, gallic acid, tannic acid, epicatechin, catechol, pyrogallol, and resveratrol.

4. The tissue adhesive material according to any one of claims 1-3, characterized in that, The mass ratio of the polymer monomer to the modified chitosan compound is (2-5):(0.5-2).

5. The tissue adhesive material according to any one of claims 1-4, characterized in that, The raw materials used in the preparation also include unmodified chitosan compounds and / or glycyrrhizic acid compounds; Preferably, the unmodified chitosan compound accounts for 2-15% of the total mass of the polymer monomer and the modified chitosan compound, and the glycyrrhizic acid compound accounts for 2-15% of the total mass of the polymer monomer and the modified chitosan compound.

6. The tissue adhesive material according to any one of claims 1-5, characterized in that, The tissue bonding material is obtained from the raw materials through a cross-linking reaction; Preferably, the tissue adhesive material is a sheet-like material; Preferably, the tissue adhesive has a breaking strength of 40 kPa or higher; and / or The swelling degree of the tissue adhesive material is below 700%.

7. A method for preparing a tissue bonding material according to any one of claims 1-6, characterized in that, Includes the following steps: The polymer monomer, modified chitosan compound, optional unmodified chitosan compound, optional glycyrrhizic acid compound and photoinitiator are dissolved in a first solvent to obtain a precursor solution; The precursor solution was subjected to a cross-linking reaction to obtain a hydrogel precursor. The hydrogel precursor is immersed in a free radical initiator solution to carry out a secondary cross-linking reaction, thereby obtaining the hydrogel primary product. The hydrogel sample is post-processed to obtain a tissue bonding material; Preferably, the primary crosslinking reaction is carried out under ultraviolet or blue light irradiation, and the primary crosslinking reaction takes 20 to 120 minutes. Preferably, the reaction temperature of the secondary crosslinking reaction is 40–80°C, and the reaction time is 10–60 min.

8. The preparation method according to claim 7, characterized in that, The method for preparing the modified chitosan compound includes modifying the chitosan compound with a polyphenol compound in the presence of a condensing agent. Preferably, the method for preparing the modified chitosan compound includes the following steps: Chitosan compounds are dissolved in a second solvent to obtain a chitosan compound solution; A polyphenolic compound is added to the chitosan compound solution to obtain the reaction solution; A condensing agent is added to the reaction solution for modification to obtain a modified chitosan compound.

9. The preparation method according to claim 7 or 8, characterized in that, The post-processing includes: The hydrogel sample was impregnated with an inorganic salt solution to obtain the impregnated product. After removing unreacted acrylic monomers and / or acrylamide monomers from the impregnation product, the tissue adhesive material is obtained by drying and sterilization. Preferably, the inorganic salt solution includes a saturated inorganic salt solution, more preferably a saturated sodium chloride solution; Preferably, a buffer solution with a pH of 7 to 8 is used to remove unreacted acrylic monomers and / or acrylamide monomers from the impregnation product.

10. The use of a tissue adhesive material according to any one of claims 1-6 in the preparation of hemostatic products, wound closure products, dura mater sealing products, vascular sealing products, lung sealing products, kidney sealing products, gastrointestinal anastomosis products, and cerebrospinal fluid leakage products.

Citation Information

Patent Citations

  • Preparation method of self-adhering super strong hydrogel

    CN108264611A

  • Modified hydroxypropyl chitosan adhesive self-healing hydrogel as well as preparation method and application thereof

    CN113861447A

  • Self-healing antibacterial tissue adhesion hydrogel, preparation method and application thereof

    CN113975451A

  • Polyacrylic acid thickening agent taking glycyrrhizic acid derivative as cross-linking agent and preparation method of polyacrylic acid thickening agent

    CN113980166A

  • Preparation method and application of wet adhesive hydrogel for dura mater damage repair

    CN114736397A